UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK SELF MANAGEMENT PADA SISWA KELAS XII IPS 4 SMA NU AL-MA'RUF KUDUS - Widyastuti, Wahyu Sri; Lestari, Indah; Sucipto, Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The purposes of this research are: 1. To describe how the implementation of group guidance services using self-management techniques is used as an effort to increase the learning motivation of class XII 4 IPS students at SMA NU Al-Ma'ruf Kudus. 2. Obtaining results of increasing learning motivation in a better direction, after carrying out self-management technique group guidance services for class XII IPS 4 SMA NU Al-Ma'ruf Kudus. Learning motivation is an encouragement that comes from outside or within students to carry out an activity related to learning with the aim of achieving the desired goals. The self-management technique group guidance service is a service that will be provided by researchers as an effort to increase the learning motivation of class XII IPS 4 SMA NU Al-Ma'ruf Kudus. The type of research used was guidance and counseling action research (PTBK). In collecting data, researchers used interview, observation techniques.